Dual‐band quasi‐self‐complementary antenna for wireless local network operation. Issue 3 (15th July 2013) - Han, T. Y.; Sim, C. Y. D.; Lai, Y. N.
ABSTRACT This article proposes a compact (6 × 21 × 0.4 mm3) antenna with dual‐band operation that satisfies the wireless local area network. To achieve optimal impedance matching for the lower and upper operating bands, the proposed antenna structure is designed as a quasi‐self‐complementary (QSC) type, in which the lower (2.4 GHz) operating band is excited through the loop‐like structure of the proposed antenna, whereas its self‐complementary counterpart (rectangular patch structure) induces the upper (5.2/5.8 GHz) operating band. Further investigation was also conducted by printing the proposed QSC antenna onto a flexible substrate of 0.063 mm in thickness. To cover both operating bands, the proposed flexible antenna was restructured to 20.5 × 8 mm2. The design and initial characteristics of the two proposed antennas were discussed in detail via simulation, and the experimental results showed satisfactory performance of both operating bands. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:298–305, 2014.